Strategy Rehabilitation and Management of Mangrove Based on SWOT Analysis in Betahwalang Village Bonang, Bonang Sub-District, Demak Regency, Central Java. - Hanik Rahmawati; Rudhi Pribadi; Adi Santoso (Journal of Marine Research, 2024)
The mangrove ecosystem in Demak District can be found one of them in Betahwalang Village, Bonang Sub District. Betahwalang Village. The management of mangrove ecosystem that is not environmentally friendly, especially in the village Betahwalang, District Bonang, Demak District This can certainly threaten the coastal area. The purpose of this study is to recommend a strategy of continuing rehabilitation and mangrove forest management in Betahwalang Village, Bonang Sub-district, Demak Regency, Central Java. This study was held in March-April 2019 in Betahwalang Village, Bonang Sub-district, Demak Regency, Central Java using descriptive method explorative. Based on the results of research obtained rehabilitation strategy and management of mangrove forest in Betahwalang Village produced 5 (five) priority is (1) active participation of the community in the efforts of mangrove rehabilitation (2) implementation Systems that are more structured for farmer groups such as the record of mangrove planting data (3) synergy between village regulations with local regulations in the efforts of mangrove rehabilitation (4) optimizing cooperation between Government and non-governmental institutions Government in the management of mangrove forests and efforts to professionals mangrove forest (5) utilization of technology and information in the management of mangrove and garbage in the area of mangrove forest.